Improving the efficacy of cancer immunotherapy by host-defence caerin 1.1 and 1.9 peptides - Quanlan Fu; Yuandong Luo; Junjie Li; Pingping Zhang; Shuxian Tang; Xinyi Song; Jiawei Fu; Mengqi Liu; Rongmi Mo; Ming Wei; Hejie Li; Xiaosong Liu; et al. (Taylor & Francis Group, 2024)
Cancer remains a major global health challenge. Immunotherapy has revolutionized the management of cancer, yet only a limited number of patients respond to such treatments. This is largely attributed to the immunosuppressive tumor microenvironment, which diminishes the effectiveness of immunotherapy. Recent studies have underscored the potential of naturally derived caerin 1 peptides, particularly caerin 1.1 and caerin 1.9, which exhibit strong antitumor effects and enhance the efficacy of immunotherapies in animal models. This review encapsulates the current research aimed at augmenting the effectiveness of immunotherapy, focusing on the role of caerin 1.1 and caerin 1.9 in boosting immunotherapeutic outcomes, elucidating possible mechanisms, and discussing their limitations and challenges.